Foot Reflexology and 4-7-8 Breathing Exercise as Supporting Therapy to Reduce Anxiety and Maintain Vital Signs of ICU Patients - Riska Cahyani Zahra; Enita Dewi; Neny Marumpy (Universitas Muhammadiyah Surakarta, 2023)
The noise of the Intensive Care Unit (ICU) equipment, the high mortality rate, the instability of other patients' conditions, and limited information increase ICU patient anxiety. Anxiety has an impact on declining health. Anxiety makes it difficult for patients to sleep, increases blood pressure values, and slows down the healing process. Management of patient anxiety is to avoid anxiety factors, use non-pharmacological and pharmacological therapies. In addition, combined pharmacological and non-pharmacological therapy is more effective in increasing patient recovery. For this reason, this study aims to evaluate the additional non-pharmacological implementation therapy of foot reflexology and 4-7-8 breathing training in patients in the ICU. The method used is a nursing practice based on evidence-based nursing implementation. The evidence-based references used are 3 international journals indexed by Scopus. The patient selection technique used purposive sampling with inclusion and exclusion criteria. Furthermore, a combination of foot reflexology intervention and 4-7-8 breathing training was given for 2 days to 3 patients. The results of the evaluation showed that there was a decrease in anxiety rates and an improvement in physiological values after being given non-pharmacological and pharmacological interventions. Improved physiological values are, blood pressure and respiratory rate. Additional non-pharmacological interventions foot reflexology and 4-7-8 breathing training reduce anxiety levels and improve the patient's physiological values.